2020
DOI: 10.1111/pace.13968
|View full text |Cite
|
Sign up to set email alerts
|

Role of cardiac sympathetic denervation in ventricular tachycardia: A meta‐analysis

Abstract: Background: Cardiac sympathetic denervation (CSD) is being used in the management of refractory ventricular tachycardia (VT) and electrical storm. However, data on the role of CSD in the management of ventricular arrhythmia is limited. Methods: We performed a meta-analysis of retrospective studies to calculate the pooled rate of freedom from VT and the standard mean difference of ICD shocks before and after CSD. Results: 14 nonrandomized studies with a total of 311 patients with refractory VT or electrical sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The authors concluded patients with NICM are more challenging for catheter ablation and would be the target population for CSD. A recent meta-analysis included 311 patients who underwent CSD for refractory VT or electrical storm and found a 60% rate of freedom from VT at a mean follow-up of 15 months ( 10 ).
Figure 2 Mechanism of Bilateral Cardiac Sympathetic Denervation in Reduction of Ventricular Arrhythmias The lower one half of the stellate ganglion and the thoracic ganglia at T1 to T4 was transected bilaterally, interrupting the sympathetic input to the heart and reducing ventricular tachycardia recurrence.
…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded patients with NICM are more challenging for catheter ablation and would be the target population for CSD. A recent meta-analysis included 311 patients who underwent CSD for refractory VT or electrical storm and found a 60% rate of freedom from VT at a mean follow-up of 15 months ( 10 ).
Figure 2 Mechanism of Bilateral Cardiac Sympathetic Denervation in Reduction of Ventricular Arrhythmias The lower one half of the stellate ganglion and the thoracic ganglia at T1 to T4 was transected bilaterally, interrupting the sympathetic input to the heart and reducing ventricular tachycardia recurrence.
…”
Section: Discussionmentioning
confidence: 99%
“…Even though this strategy is still highly restricted to a few “expertise centers,” the number and size of clinical studies is ever expanding. The success of this treatment modality was reconfirmed in a meta-analysis by Murtaza et al [ 101 ] which combined the results of 14 retrospective clinical studies that included a total of 311 patients with recurrent ventricular tachycardia or electrical storm. Their analyses showed that CSD resulted in complete abolishment of ventricular tachycardia in approximately 60% of treated patients (average follow-up time: 15 ± 10.7 months) and a significant decrease of 3.01 in mean implantable cardioverter-defibrillator (ICD) shocks [ 101 ].…”
Section: Interventionsmentioning
confidence: 98%
“…The success of this treatment modality was reconfirmed in a meta-analysis by Murtaza et al [ 101 ] which combined the results of 14 retrospective clinical studies that included a total of 311 patients with recurrent ventricular tachycardia or electrical storm. Their analyses showed that CSD resulted in complete abolishment of ventricular tachycardia in approximately 60% of treated patients (average follow-up time: 15 ± 10.7 months) and a significant decrease of 3.01 in mean implantable cardioverter-defibrillator (ICD) shocks [ 101 ]. Importantly, these results of CSD efficacy are similar between patients with and without an ischemic substrate underlying their ventricular arrhythmias [ 102 , 103 ].…”
Section: Interventionsmentioning
confidence: 98%
“… 59 Modulation of the autonomic nervous system and neuraxial blockade are important therapies for electrical storm 60 and are an established component of antiarrhythmic therapy for specific genetic syndromes, including long QT syndrome. 61 Emerging data suggest that autonomic modulation may be an effective tool in the broader population of secondary prevention patients, 62 though more data are needed.…”
Section: Novel Strategies For Arrhythmia Risk Reductionmentioning
confidence: 99%